Civil Society as the Fifth Estate: Civil Society, Media Reform and Democracy in Korea - Kwak, Ki-Sung (Television, Regulation and Civil Society in Asia, 2002)
Since the Korean War (1950-53), South Korea (hereafter Korea) has undergone a series of political changes. The move towards democratisation was largely spurred on by the demonstrations and riots occurring throughout the 1980s. In 1987 massive demonstrations forced the then President Chun DooHwan to call a new presidential election, and President-elect Rho Tae-Woo to implement more social reforms. The notion of civil society in Korea has been a relatively new concept until very recently, mainly because it has not achieved wide recognition from the public, media or the state. The development of a people’s movement advocating democracy could be said to be the foundation of ‘civil society’ in Korea.
Keywords: 1-TV; 2-Approches sociologiques; 2-Histoire/Historiographie critique; 2-Théorie(s) et épistémologies des médias (media studies/médiologie/intermédialités); 2-Étude des industries culturelles; 3-Asie (corpus analysé); 4-Océanie (lieu de production du savoir); 5-Auteur.rice PANDC; Australie (lieu de production du savoir); Corée du Sud (corpus analysé); _Nettoyé

Television in the Formation of Civil Society: The Role of a Non- Controversial Public Space in Hong Kong - Lee, Paul S. N. (Television, Regulation and Civil Society in Asia, 2002)
Television first appeared in Hong Kong in 1957. It was a cable television service run by the Rediffusion Company which had operated a highly successful wired sound broadcasting service since 1949. Hong Kong was the first British colony to have television. But the Rediffusion television service was very expensive. Its monthly subscription fee was HK$55. In 1958, a technical worker’s monthly wages were HK$360 and an unskilled worker earned only HK$75 (Hong Kong Government 1959: 32). A year before the introduction of free-to-air television in 1967, Rediffusion television had only 67,000 subscribers (Hong Kong Government 1967: 206). Thus before 1967 television was an elite medium and its social impact was minimal.
Keywords: 1-TV; 2-Approches sociologiques; 2-Histoire/Historiographie critique; 2-Théorie(s) et épistémologies des médias (media studies/médiologie/intermédialités); 2-Étude des industries culturelles; 3-Asie (corpus analysé); 4-Asie (lieu de production du savoir); 5-Auteur.rice PANDC; Hong Kong (corpus analysé); Hong Kong (lieu de production du savoir); _Nettoyé

Out of Reach: Television, the Public Sphere and Civil Society in the Philippines - Santos, Josefina M. C. (Television, Regulation and Civil Society in Asia, 2002)
In the uprising of 16-20 January 2001, which ousted former Philippine President Joseph Estrada from power, two forces stood out as pivotal: television (specifically the coverage of the impeachment trial which was the centre of public attention) and civil society (which was instrumental in the uprising itself). In this chapter I argue that notwithstanding the central importance of television in this most recent national political change, the regulation of the sector and its long-term associations with crony capitalism have established barriers to civil society finding its voice on television.
Keywords: 1-TV; 2-Approches sociologiques; 2-Histoire/Historiographie critique; 2-Théorie(s) et épistémologies des médias (media studies/médiologie/intermédialités); 2-Étude des industries culturelles; 3-Asie (corpus analysé); 4-Asie (lieu de production du savoir); 5-Auteur.rice PANDC; 5-Autrice; Philippines (corpus analysé); Philippines (lieu de production du savoir); _Nettoyé

Changing Contexts, New Texts: ‘‘Inserting’’ TV into the Transforming Text of Post-1980 Bengali Cinema - Gooptu, Sharmistha (Television in India: Satellites, Politics and Cultural Change, 2008)
This chapter analyses a profound transformation of Bengali regional-languagecinema since the early 1980s, a transformation that fundamentally changedthe industry and one that can arguably be attributed at least partly to thecreation of a Bengali television-watching public in the same period. Itfocuses on a trend that emerged in mainstream Bengali cinema during the1980s and was sustained thereafter, and brought into prominence a newconfiguration of elements previously marginal to Bengali films. This trans-formation was to do with mainstream Bengali cinema’s increasing adaptation of what are commonly known as the ‘‘masala’’ or ‘‘formula’’ elementsof Bombay cinema such as racy dialogues, stereotypical villainous char-acters, stylized fights and song-and-dance sequences. This new genre, whichhas commonly been discredited as the Bengali film industry’s totally unim-aginative imitation of the popular Hindi-language cinema of Bombay,completely altered what had been the dominant aesthetic of Bengali cinematill about the mid-1970s. Until this point, Bengali cinema was marked by itsclose relationship with Bengali literature and a Bengali middle-class worldview, greater realism than Bombay cinema or other mainstream regionalcinemas, and naturalistic acting styles, and was radically transformed by agrowing adoption of the ‘‘formula’’ elements commonly identified withpopular Hindi cinema. Industry sources, however, indicate that this newtrend was successful in boosting the Bengali film industry, which had beenswamped by a severe economic crisis since the 1970s. The industry’s crisiswas caused by a host of factors: the most important of these was the Ben-gali middle-class audience’s shift to television as a result of an increasingly unsatisfactory film-going experience in this period. The creation of a Ben-gali television public in the early 1980s shifted audiences from the cinematheatres, thereby significantly reducing film revenues in Calcutta, until then the prime market for Bengali films.
Keywords: 1-Cinéma; 1-TV; 2-Analyses formalistes; 2-Approches sociologiques; 2-Histoire/Historiographie critique; 2-Étude des industries culturelles; 2-Étude des représentations; 3-Asie (corpus analysé); 4-Asie (lieu de production du savoir); 5-Auteur.rice PANDC; 5-Autrice; Inde (corpus analysé); Inde (lieu de production du savoir); _Nettoyé

Soaps, Serials and the CPI(M), Crickets Beat Them All: Cricket and Television in Contemporary India - Majumdar, Boria (Television in India: Satellites, Politics and Cultural Change, 2008)
The changing relationship between cricket and satellite television in thecontext of the Indian sub-continent has been a subject of considerablescholarly inquiry. That one nourishes the other is well known. However,what is relatively little known is the degree to which this interdependence hasgrown in recent times. So much so that cricket tournaments, or ratherdesignated TV tournaments, are being planned with alacrity by the Board ofControl for Cricket in India (BCCI). Television rights for these overseastournaments/matches spread over the next 4 years had initially generated $219.5 million for the BCCI.1 On the other hand, satellite channels too havestarted planning cricket programming around these tournaments, program-ming expected to generate millions in advertising revenue.2 While theorganization of such big-money events well encapsulates the symbiotic rela-tionship between cricket and satellite television within a burgeoning Indianeconomy, other local/regional dimensions of this relationship are often noless fascinating. Tele-visual hype generated on the occasion of a regionalcricket body election in July 2006 in West Bengal, especially by the multiple 24-hour Bengali news channels, drew attention to the local variant of thestory involving big-money television and even bigger-money sport. Thischapter, on the basis of two distinct case studies – the implications of the tri-nation 1-day series played in Malaysia in September 2006 involving Aus-tralia, West Indies and India, and Television coverage of the Cricket Asso-ciation of Bengal Elections in July 2006 – will comment on the complex andever-changing relationship between cricket and television in India. At thesame time it will attempt to question the rationale behind this growing interdependence and probe what this means for the Indian nation at large.
Keywords: 1-TV; 2-Approches sociologiques; 2-Histoire/Historiographie critique; 2-Théorie(s) et épistémologies des médias (media studies/médiologie/intermédialités); 2-Étude des industries culturelles; 3-Asie (corpus analysé); 4-Océanie (lieu de production du savoir); 5-Auteur.rice PANDC; Australie (lieu de production du savoir); Inde (corpus analysé); _Nettoyé

India Talking: Politics, Democracy and News Television - Mehta, Nalin (Television in India: Satellites, Politics and Cultural Change, 2008)
After four decades of state monopoly over television Indian viewers gottheir first taste of private television in the early 1990s. By 1998, the first of India’s private 24-hour news channels was on the airwaves and by 2007more than 300 satellite channels were broadcasting into Indian homes. Ofthese, 106 broadcast news in 14 languages and as many as 54 of these were24-hour news channels in 11 languages.1 These are conservative figures thatdo not include many foreign and local cable networks that also broadcastnews.2 Even so, the numbers are a stark illustration of how the Indian statelost control over television broadcasting despite its best efforts to the con-trary. No other country in the world has such a concentration of private news channels as India. The creation of a television public has significantimplications for democracy and this essay focuses on what 24-hour newsmeans for India. It argues that the emergence of television news networkshas greatly enhanced and strengthened deliberative Indian democracy.Commercial mass media stands at the junction of politics and the economy,enabling the entry of citizens onto the stage of politics, while simultaneouslyseeking to appropriate that energy for its own commercial benefit (Rajago-pal, 1999: 133). This is a claim that needs to be differentiated from the usual journalistic self-image of the fourth estate acting as vigilant defenders ofdemocratic ideals. That notion should not be romanticised too muchbecause news production itself is a cultural process that cannot be separatedfrom its social environment. News producers always function under certaininstitutional constraints that are endemic to the news-gathering process.Leftist and liberal scholars of the media differ in their emphasis but allagree that news production is always circumscribed by institutional filters.3News is ‘more a pawn of shared suppositions than the purveyor of selfconscious messages’ (Schudson, 1995: 15). Yet, the media are important,and while it is difficult to draw direct causal linkages, there is no doubt thatthey initiate and create a new sphere of political action.
Keywords: 1-TV; 2-Approches sociologiques; 2-Histoire/Historiographie critique; 2-Théorie(s) et épistémologies des médias (media studies/médiologie/intermédialités); 2-Étude des industries culturelles; 2-Étude des représentations; 3-Asie (corpus analysé); 4-Asie (lieu de production du savoir); 5-Auteur.rice PANDC; 5-Identités diasporiques; Inde (corpus analysé); Singapour (lieu de production du savoir); _Nettoyé

Television in Post-Reform China: Serial Dramas, Confucian Leadership and the Global Television Market - Zhu, Ying (Routledge, 2008)
This book explores the political, economic, and cultural forces, locally and globally that have shaped the evolution of Chinese primetime television dramas, and the way that these dramas in turn have actively engaged in the major intellectual and policy debates concerning the path, steps, and speed of China’s economic and political modernization during the post-Deng Xiaoping era. It intertwines the evolution of Chinese television drama particularly with the ascendance of the Chinese New Left that favors a recentralization of state authority and an alternative path towards China’s modernization and China’s current administration’s call for building a "harmonious society." Two types of serial drama are highlighted in this regard, the politically provocative dynasty drama and the culturally ambiguous domestic drama. The book also provides cross-cultural comparisons that parallel the textual and institutional strategies of transnational Chinese language TV dramas with dramas from the three leading centers of transnational television production, the US, Brazil and Mexico in Latin America, and the Korean-led East Asia region. The comparison reveals creative connections while it also explores how the emergence of a Chinese cultural-linguistic market, together with other cultural-linguistic markets, complicates the power dynamics of global cultural flows.
Keywords: 1-TV; 2-Approches sociologiques; 2-Genre et sexualité; 2-Histoire/Historiographie critique; 2-Étude des industries culturelles; 2-Étude des représentations; 3-Asie (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 5-Auteur.rice PANDC; 5-Autrice; Chine (corpus analysé); _Nettoyé; États-Unis (lieu de production du savoir)

Culture, Politics, and Television in Hong Kong - Ma, Eric Kit-wai (Routledge, 1999)
Ma looks at the ways in which the identity of Hong Kong citizens has changed in the 1990s especially since the handover to China in 1997. This is the first analysis which focuses on the role, in this process, of popular media in general and television in particular. The author specifically analyses at the relationship between television ideologies and cultural identities and explores the role of television in the process of identity formation and maintenance.
Keywords: 1-TV; 2-Approches sociologiques; 2-Histoire/Historiographie critique; 2-Théorie(s) et épistémologies des médias (media studies/médiologie/intermédialités); 2-Étude des industries culturelles; 2-Étude des représentations; 3-Asie (corpus analysé); 4-Asie (lieu de production du savoir); 5-Auteur.rice PANDC; Hong Kong (corpus analysé); Hong Kong (lieu de production du savoir); _Nettoyé

Television Regulation and Media Policy in China - Chin, Yik-Chan (Routledge, 2016)
Since the late 1990s, there has been a crucial and substantial transformation in China’s television system involving institutional, structural and regulatory changes. Unravelling the implications of these changes is vital for understanding the politics of Chinese media policy-making and regulation, and thus a comprehensive study of this history has never been more essential. This book studies the transformation of the policy and regulation of the Chinese television sector within a national political and economic context from 1996 to the present day. Taking a historical and sociological approach, it engages in the theoretical debates over the nature of the transformation of media in the authoritarian Chinese state; the implications of the ruling party’s political legitimacy and China’s central-local conflicts upon television policy-making and market structure; and the nature of the media modernisation process in a developing country. Its case studies include broadcasting systems in Shanghai and Guangdong, which demonstrate that varied polices and development strategies have been adopted by television stations, reflecting different local circumstances and needs. Arguing that rather than being a homogenous entity, China has demonstrated substantial local diversity and complex interactions between local, national and global media, this book will be of interest to students and scholars of Chinese media, politics and policy, and international communications.
Keywords: 1-TV; 2-Approches sociologiques; 2-Histoire/Historiographie critique; 2-Théorie(s) et épistémologies des médias (media studies/médiologie/intermédialités); 2-Étude des industries culturelles; 2-Étude des représentations; 3-Asie (corpus analysé); 4-Asie (lieu de production du savoir); 5-Auteur.rice PANDC; 5-Autrice; Chine (corpus analysé); Chine (lieu de production du savoir); _Nettoyé

Taiyu Serial Dramas in Taiwan: A History of Problem-Making - Irene Yang, Fang-Chih (Television Histories in Asia, 2015)
The construction of a problem, be it a crisis or a moral panic, is an attempt of policing and control, for the maintenance of hegemony and authority (Hall et al. 1978 ). A problem emerges as a problem only when it is out of its proper place, just like dirt becomes dirt only when it is not properly placed in the earth. The elimination of dirt is necessary in maintaining the cleanliness of the social order (Douglas 2002 ). In other words, it is the need for a particular social arrangement that constitutes the existence of a problem. Taiyu, the lingua franca of the Taiwanese, became a problem of dialect (called Minnanyu) to be eliminated when the KMT colonial regime moved to Taiwan, building it as a Chinese nation and instituting Mandarin as the national language. Television is central to the building of the Chinese nation. Taiyu serial dramas were broadcast soon after the fi rst network was established in 1962, but have been constructed as the most problematic and debased genre since the early 1970s when the second TV station, CTV (1969), and the third, CTS (1971), were established and used serial drama to compete for profi t. Accusations directed at the poverty of its quality and the vulgarity of the audiences have characterized mainstream criticisms and constructions of Taiyu serial dramas as problems from the 1970s to the present. This chapter investigates not only the how and what but also the why of this problem-construction, as an attempt to understand the power mechanisms at work in struggling for hegemonic control. It charts two historical moments – the 1970s and from the 1990s to the present – when language has played a signifi cant role in the articulations of serial dramas as problems and explores the changing political, economic and cultural forces that situate them as problems worthy of discussion. I argue that the history of this problem-making demonstrates the centrality of Chinese culture in political domination through cultural means, with ethnic/class politics playing a central role in the maintenance of a hierarchical social order. In the 1970s, Chinese culture was used to create ethnic/class divisions within Taiwan while simultaneously creating the illusion of a symbolic whole under the name of the Republic of China. However, since the 1990s, and intensifying after the 2000s, with the entanglement of democratization and neoliberalization in Taiwan and the rise of China, the ethnic/class tension is not just complicated by confl icted national identifi cations and Chinese culturepromoted by both the KMT Party’s Republic of China and the People’s Republic of China, but also for unifi cation purposes. While democratization, which involved the search for Taiwanese identity, led to the rise of Taiyu-based Hsiangtu drama, the neoliberal defi nition of culture as economic resource, which consecrates Chinese culture through capital investment, facilitates this unifi cation process while creating further ethnic/class/national identity divisions within Taiwan. The result is a disparaging of Taiyu-based culture in general and, in particular, Taiyu serial drama as a problem to be reformed.
Keywords: 1-TV; 2-Approches sociologiques; 2-Histoire/Historiographie critique; 2-Méthodologie de recherche décoloniale; 2-Étude des industries culturelles; 2-Étude des représentations; 3-Asie (corpus analysé); 4-Asie (lieu de production du savoir); 5-Auteur.rice PANDC; 5-Autrice; Taiwan (corpus analysé); Taiwan (lieu de production du savoir); _Nettoyé

The Television of Intervention: Mediating Patron–Client Ties in the Philippines - Corpus Ong, Jonathan (Television Histories in Asia: Issues and Contexts, 2015)
Similar to the other countries discussed in this volume, elite dominance over mass media has been a main characteristic of Filipino history. Foreign-educated Filipino intellectuals from wealthy families founded the early periodicals that demanded reform and/or independence from Spanish colonization in the late nineteenth century (Anderson 1983 ). Today, ‘old rich’ landowning families own and operate television networks, radio stations, and newspapers not only as part of prestigious and profi table media conglomerates, but also in connection with their interests in industries as varied as oil and agriculture to insurance, shipping, and mining.
Keywords: 1-TV; 2-Approches sociologiques; 2-Histoire/Historiographie critique; 2-Étude de la réception; 2-Étude des industries culturelles; 3-Asie (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 5-Auteur.rice PANDC; Philippines (corpus analysé); _Nettoyé; États-Unis (lieu de production du savoir)

Television, Scale and Place-Identity in the PRC: Provincial, National and Global Influences from 1958 to 2013 - Sun, Wanning; Gorfinkel, Lauren (Television Histories in Asia: Issues and Contexts, 2015)
One may argue that Chinese television has already received more than its fair share of attention in the study of Chinese media. As compared with radio and cinema, which developed in the socialist era (1949-78), television has been seen as the dominant medium in the decades of marketization and economic reforms since the late 1970s (Zhu and Berry 2008 ). Television has been studied as a metonym for the ongoing tension and complicity between the Chinese state and the market (e.g., Zhao 1998 ; 2008a) and as a metaphor for the contradictions between a legacy of socialist rhetoric and ethos and a neoliberal market agenda. It is precisely these contradictions that make up what is often referred to as the ‘Chinese characteristics’ (Zhao 2008a; Sun and Zhao 2009 ) of China’s television culture.
Keywords: 1-TV; 2-Approches sociologiques; 2-Histoire/Historiographie critique; 2-Théorie(s) et épistémologies des médias (media studies/médiologie/intermédialités); 2-Étude des industries culturelles; 3-Asie (corpus analysé); 4-Océanie (lieu de production du savoir); 5-Auteur.rice PANDC; 5-Autrice; Australie (lieu de production du savoir); Chine (corpus analysé); _Nettoyé

Reality Television and the Making of Mobile Publics: The Case of Indian Idol - Punathambekar, Aswin (The Politics of Reality Television: Global Perspectives, 2010)
In the summer of 2007, media coverage of Indian Idol-3 focused attention on how people in the Northeast Indian state of Meghalaya cast aside decades-old separatist identities to mobilize support for Amit Paul, a ﬁnalist from the region. While some fans set up websites and blogs to generate interest and support from the rest of the country and abroad, others formed a fan club and facilitated eﬀorts by a range of groups and organizations to sponsor and manage PCOs (public call oﬃces) in diﬀerent parts of Meghalaya, distribute pre-paid mobile phone cards, and set up landline voting booths. Recognizing the ways in which these activities were beginning to transcend long-standing ethnic, religious, linguistic, and spatial boundaries, state legislators and other politicians soon joined the eﬀort to garner votes for Amit Paul, with the chief minister D. D. Lapang declaring Amit Paul to be Meghalaya’s “brand Ambassador for peace, communal harmony and excellence.”1 It seemed that this three-month-long campaign around a reality television program could set the stage for a remarkable refashioning of the socio-cultural and political terrain in Meghalaya. As one commentator remarked:When Meghalaya’s history is written, it could well be divided into two distinct phases – one before the third Indian Idol contest and one after it. A deep tribal-non-tribal divide, punctuated by killings, riots, and attempts at ethnic cleansing, would mark the ﬁrst phase. A return to harmony and to the cosmopolitan ethos of the past would signify the second. The agent of change: Amit Paul, the ﬁnalist of the musical talent hunt on a TV channel.
Keywords: 1-TV; 2-Approches sociologiques; 2-Histoire/Historiographie critique; 2-Théorie(s) et épistémologies des médias (media studies/médiologie/intermédialités); 3-Asie (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 5-Auteur.rice PANDC; Inde (corpus analysé); _Nettoyé; États-Unis (lieu de production du savoir)

Tears, Talk, and Play: A Window to Gender and Sexuality on Tamil Television - Vangal, Uma (Channeling Cultures: Television Studies from India, 2014)
Tamil television lends itself to some interesting initiatives in gender empowerment through its programming in 3 categories – fiction, reality, and talent shows. This chapter provides a glimpse into television programmes on leading Tamil channels over the last decade (2000–10) from a gender perspective. Focusing particularly on women and transgender characters/hosts, emotional and psychological quotients of the shows and their audiences, moments of dramatic intensity, the chapter demonstrates how the vernacular televisual representations were quite different from the stereotypical portrayals of the mainstream ‘national’ television, even though the programmes were produced, televised, and received within the broader patriarchal framework of Tamil cultural and political contexts. The chapter, as a whole, intends to look at the production, representation and identification of Tamil television soaps and reality shows as vehicle for spotlighting gender issues and alternative sexualities in the public domain.
Keywords: 1-TV; 2-Approches sociologiques; 2-Genre et sexualité; 2-Histoire/Historiographie critique; 2-Étude des industries culturelles; 2-Étude des représentations; 3-Asie (corpus analysé); 4-Asie (lieu de production du savoir); 5-Auteur.rice PANDC; 5-Autrice; Inde (corpus analysé); Inde (lieu de production du savoir); _Nettoyé

When Live News was Too Dangerous: The Early History of Satellite TV in India - Mehta, Nalin (Channeling Cultures: Television Studies from India, 2014)
A unique confluence of technological, political and economic factors in the 1990s drove the transformative process that led to the battering down of the government’s monopoly over television. By the end of the 1990s, the growing strength of Indian capitalism after the liberalization of the Indian economy and the forces of what Thomas Friedman has called ‘Globalisation 3.0’ allowed Indian entrepreneurs to level the playing field. The Indian state, having embarked on economic liberalization, was forced to adapt to satellite television as an agent of global capitalism it certainly did not give up control over television easily or voluntarily. Operating at the junction of public culture, capitalism and globalization, satellite news networks have had profound implications for the state, politics, democracy and identity formation. Despite all their shortcomings and sensationalism, the emergence of satellite television news networks has enhanced and strengthened deliberative Indian democracy.
Keywords: 1-TV; 2-Histoire/Historiographie critique; 2-Théorie(s) et épistémologies des médias (media studies/médiologie/intermédialités); 2-Étude des industries culturelles; 3-Asie (corpus analysé); 4-Asie (lieu de production du savoir); 5-Auteur.rice PANDC; Inde (corpus analysé); Inde (lieu de production du savoir); _Nettoyé

Television News and an Indian Infotainment Sphere - Thussu, Daya Kishan (Channeling Cultures: Television Studies from India, 2014)
The exponential growth of television news in India – from one state controlled network until 1991 to more than 100 news channels in 2012 – has transformed broadcast journalism in the country. This proliferation of news networks has intensified competition for audience and advertising revenue, leading to excessive marketization of news, which increasingly veers toward infotainment. The chapter examines the challenges faced by Indian television news – focusing on economic and political dimensions of television news - and its implications for the world’s largest democracy.
Keywords: 1-TV; 2-Approches sociologiques; 2-Histoire/Historiographie critique; 2-Théorie(s) et épistémologies des médias (media studies/médiologie/intermédialités); 2-Étude des industries culturelles; 3-Asie (corpus analysé); 4-Asie (lieu de production du savoir); 5-Auteur.rice PANDC; Hong Kong (lieu de production du savoir); Inde (corpus analysé); _Nettoyé

TV after Television Studies: Recasting Questions of Audiovisual Form - Roy, Abhijit (Channeling Cultures: Television Studies from India, 2014)
This chapter locates India, and broadly the post-colonial context, within the larger debates concerning television’s audiovisual form and mode of address. It tries to demonstrate that certain key traits in Indian popular performative traditions, representing an ‘alternative’ negotiation with modernity, are somewhat homologous with what western theorists have tried to specify (though in contradicting terms) as the features of televisual mode of address and ‘flow’. The chapter reads the specific imports of this correspondence in histories of Indian television with special reference to a somewhat novel way television has started imagining the nation after liberalization. The significance of the Indian popular film form as lending a major legacy to tele-viewership in India constitutes a major strand of argument.
Keywords: 1-TV; 2-Approches sociologiques; 2-Histoire/Historiographie critique; 2-Étude des industries culturelles; 3-Asie (corpus analysé); 4-Asie (lieu de production du savoir); 5-Auteur.rice PANDC; Inde (corpus analysé); Inde (lieu de production du savoir); _Nettoyé

Copied from Without and Cloned from Within: India in the Global Television Format Business - Thomas, Amos Owen; Kumar, Keval J. (Television Across Asia: TV Industries, Programme Formats and Globalisation, 2003)
Television programme format adaptation is becoming an increasingly signiﬁcant phenomenon in India as it is in many other countries with an active domestic television industry. Some obvious successes stand out in recent years, such as Kaun Banega Crorepati, the licensed adaptation of Celador’s global format success Who Wants To Be A Millionaire?, and C.A.T.S., a licensed Hindi version of the US detective series Charlie’s Angels. However, sensitivity to local cultural nuances has been critical to their popular reception by Indian audiences. Yet despite a few high-proﬁle licensed adaptations or copycatting, there are far more instances of unlicensed adaptations or cloning, sometimes subtle, other times not.
Keywords: 1-TV; 2-Analyses formalistes; 2-Histoire/Historiographie critique; 2-Étude des industries culturelles; 3-Asie (corpus analysé); 4-Asie (lieu de production du savoir); 4-Europe (lieu de production du savoir); 5-Auteur.rice PANDC; Inde (corpus analysé); Inde (lieu de production du savoir); Suède (lieu de production du savoir); _Nettoyé

Globalization and Television: A Study of the Indian Experience, 1990-2010 - Narayan, Sunetra Sen (Oxford University Press, 2013)
This study explores the globalization and liberalization that has occurred in Indian television over the two decades starting from 1990.
Keywords: 1-TV; 2-Approches sociologiques; 2-Histoire/Historiographie critique; 2-Théorie(s) et épistémologies des médias (media studies/médiologie/intermédialités); 2-Étude des industries culturelles; 3-Asie (corpus analysé); 4-Asie (lieu de production du savoir); 5-Auteur.rice PANDC; 5-Autrice; Inde (corpus analysé); Inde (lieu de production du savoir); _Nettoyé

Television in Post-Reform Vietnam: Nation, Media, Market - Nguyen-Thu, Giang (Routledge, 2018)
This book explores Vietnamese popular television in the post-Reform era, that is, from 1986, focussing on the relationship between television and national imagination. It locates Vietnamese television in the experiences of everyday life and the prevailing network of power relations resulting from marketization and globalization, and, as such, moves beyond the clichéd assumption of Vietnamese media as a mere propagandist instrument of the party state. With examples from a wide range of television genres, the book demonstrates how Vietnamese television enables novel conditions of cultural oppression as well as political engagement in the name of the nation. In sharp contrast to the previous image of Vietnam as a war-torn land, post-Reform television conjures into being a new sense of national belonging based on an implicit rejection of the socialist past, hopes for peace and prosperity, and anxieties about a globalized future. This book highlights the richness of Vietnam’s current culture and identity, characterized, the book argues, by ‘fraternity without uniformity’.
Keywords: 1-TV; 2-Approches sociologiques; 2-Histoire/Historiographie critique; 2-Étude des industries culturelles; 2-Étude des représentations; 3-Asie (corpus analysé); 4-Océanie (lieu de production du savoir); 5-Auteur.rice PANDC; 5-Autrice; 5-Identités diasporiques; Australie (lieu de production du savoir); Vietnam (corpus analysé); _Nettoyé

The Little Emperors’ New Toys: A Critical Inquiry into Children and Television in China - Zhao, Bin (Springer, 2013)
Drawing on original research I conducted in the late 1980s, the book argues for a critical approach to the study of children and television. It begins with critical reappraisals of previous empiricist and interpretative studies to set the ground for a different theoretical inquiry which links biography with history. The situated activity of children's television viewing therefore has to be related to the broader historical and cultural formations in post-Mao China. By way of a methodological pluralism of questionnaire survey, in-depth interviews and observation, the book provides the reader with a thorough critical analysis of the rise of the new commercial ethic in Chinese society in general, and in the sector of media and communications in particular, at the very historical turning point of the late 1980s. Soon after that, Deng Xiaoping made his significant tour to south China, reckoning a big step forward towards further liberalization and started to form a brave new world in China ever since.
Keywords: 1-TV; 2-Approches sociologiques; 2-Histoire/Historiographie critique; 2-Théorie(s) et épistémologies des médias (media studies/médiologie/intermédialités); 2-Étude de la réception; 2-Étude des industries culturelles; 3-Asie (corpus analysé); 4-Asie (lieu de production du savoir); 5-Auteur.rice PANDC; Chine (corpus analysé); Chine (lieu de production du savoir); _Nettoyé

Pimpin' Ain't Easy: Selling Black Entertainment Television - Smith-Shomade, Beretta E. (Routledge, 2007)
Launched in 1980, cable network Black Entertainment Television (BET) has helped make blackness visible and profitable at levels never seen prior in the TV industry. In 2000, BET was sold by founder Robert L. Johnson, a former cable lobbyist, to media giant Viacom for 2.33 billion dollars. This book explores the legacy of BET: what the network has provided to the larger US television economy, and, more specifically, to its target African-American demographic. The book examines whether the company has fulfilled its stated goals and implied obligation to African-American communities. Has it changed the way African-Americans see themselves and the way others see them? Does the financial success of the network - secured in large part via the proliferation of images deemed offensive and problematic by many black communities - come at the expense of its African-American audience? This book fills a major gap in black television scholarship and should find a sizeable audience in both media studies and African-American studies.
Keywords: 1-TV; 2-Approches sociologiques; 2-Histoire/Historiographie critique; 2-Étude des industries culturelles; 2-Étude des représentations; 3-Amérique du Nord (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 5-Auteur.rice PANDC; 5-Auteur.rice noir.e; 5-Autrice; _Nettoyé; États-Unis (corpus analysé); États-Unis (lieu de production du savoir)

Television in Bangladesh: News and Audiences - Roy, Ratan Kumar (Routledge India, 2020)
This book examines the role of 24/7 television news channels in Bangladesh. By using a multi-sited ethnography of television news media, it showcases the socio-political undercurrents of media practices and the everydayness of TV news in Bangladesh. It discusses a wide gamut of issues such as news making; localised public sphere; audience reaction and viewing culture; impact of rumours and fake news; socio-political conditions; protest mobilization; newsroom politics and perspectives from the ground. An important intervention in the subject, this book will be useful to scholars and researchers of media studies, journalism and mass communication, anthropology, cultural studies, political sociology, political science, sociology, South Asian studies, as well as television professionals, journalists, civil society activists, and those interested in the study of Bangladesh.
Keywords: 1-TV; 2-Approches sociologiques; 2-Histoire/Historiographie critique; 2-Théorie(s) et épistémologies des médias (media studies/médiologie/intermédialités); 2-Étude de la réception; 2-Étude des industries culturelles; 3-Asie (corpus analysé); 4-Asie (lieu de production du savoir); 5-Auteur.rice PANDC; Bangladesh (corpus analysé); Inde (lieu de production du savoir); _Nettoyé

Producing Domestic Abuse in Pakistani Television: Between Commerce, Ratings and Social Responsibility - Cheema, Munira (Television for Women, 2016)
Before the liberalisation of television in 2000, Pakistan had one terrestrial channel.The Pakistan Television Corporation (commonly known as PTV) had been the statebroadcaster since 1964 and thus PTV content reflected the policies of differentgovernments. Liberal governments relaxed control over gender on screen – womencould be seen without dupatta – while religiously inclined governments brought intheir own agendas with restrictions on appearance of women, such as the dupattapolicy (see, for example, Ali, 1986; Suleman, 1990; Kothari, 2005; Nasir, 2012).1 In2002, the Independent Media Corporation launched its channel Geo News fromPakistan, followed by other networks, marking the formal launch of the policy ofliberalisation of media on television. Presently, five media groups have control of thePakistani media industry, including electronic and print media. These are Inde-pendent Media Corporation, Pakistan Herald Publications, ARY Group, WaqtGroup and Lakson Group (see for example Proffitt and Rasul, 2013). The broad-casting industry in Pakistan follows an advertiser-driven model that is run through asystem of ratings. At the time of the fieldwork reported here (October-April 2011),Media Logic and Gallup were the two operators that determined the popular tastesof consumers through ratings.2
Keywords: 1-TV; 2-Approches sociologiques; 2-Genre et sexualité; 2-Histoire/Historiographie critique; 2-Théorie(s) et épistémologies des médias (media studies/médiologie/intermédialités); 2-Étude des industries culturelles; 2-Étude des représentations; 3-Asie (corpus analysé); 5-Auteur.rice PANDC; 5-Autrice; Pakistan (corpus analysé); _Nettoyé

Shaded Lives: African-American Women and Television - Smith-Shomade, Beretta E. (Rutgers University Press, 2002)
Since its invention, television has been one of the biggest influences on American culture. Through this medium, multiple visions and disparate voices have attempted to stake a place in viewer consumption. Yet even as this programming supposedly reflects characteristics of the general American populace, television-generated images are manipulated and contradictory, predicated by the various economic, political, and cultural forces placed upon it. In Shaded Lives, Beretta Smith-Shomade sets out to dissect images of the African American woman in television from the 1980s. She calls their depiction "binaristic," or split. African American women, although an essential part of television programming today, are still presented as distorted and deviant. By closely examining the television texts of African-American women in comedy, music video, television news and talk shows (Oprah Winfrey is highlighted), Smith-Shomade shows how these voices are represented, what forces may be at work in influencing these images, and what alternate ways of viewing might be available. Smith-Shomade offers critical examples of where the sexist and racist legacy of this country collide with the cultural strength of Black women in visual and real-lived culture. As the nation's climate of heightened racial divisiveness continues to relegate the representation of Black women to depravity and display, her study is not only useful, it is critical.
Keywords: 1-TV; 2-Approches sociologiques; 2-Genre et sexualité; 2-Histoire/Historiographie critique; 2-Étude des représentations; 3-Amérique du Nord (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 5-Auteur.rice PANDC; 5-Auteur.rice noir.e; 5-Autrice; _Nettoyé; États-Unis (corpus analysé); États-Unis (lieu de production du savoir)

Is She Strong or Just a B!@*#? Discussion of Black Women's Anger in the Reality Show Bad Girls Club - Goldman, Adria Y. (Black Women's Portrayals on Reality Television: The New Sapphire, 2016)
It is near impossible to have a discussion of black women in reality television without mentioning the infamous Angry Black Woman (ABW). In fact, some critiques have argued reality television is damaging for black women since many shows focus heavily on this character. 1 This stereotypical characterization of black women is long-standing, due largely to its constant inclusion in media messages. As noted in chapter one, audiences were first officially introduced to her in the 1920s as Sapphire Stevens from the Amos ‘n’ Andy Show ; and her character continued to resurface throughout the years, across several different genres. Despite the many time periods through which this image has traveled, the key characteristic of the Sapphire— her unexplainable anger and aggression— seem to resonate in many modern day images of black women.
Keywords: 1-TV; 2-Approches sociologiques; 2-Genre et sexualité; 2-Histoire/Historiographie critique; 2-Étude des représentations; 3-Amérique du Nord (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 5-Auteur.rice PANDC; 5-Auteur.rice noir.e; 5-Autrice; _Nettoyé; États-Unis (corpus analysé); États-Unis (lieu de production du savoir)

The A to Z of African-American Television - Fearn-Banks, Kathleen (Scarecrow Press, 2009)
From Amos 'n' Andy to The Jeffersons to Family Matters to Chappelle's Show, this volume covers it all with entries on all different genres_animation, documentaries, sitcoms, sports, talk shows, and variety shows_and performers such as Muhammad Ali, Louis Armstrong, Bill Cosby, and Oprah Winfrey. Additionally, information can be found on general issues, ranging from African American audiences and stereotypes through the related networks and organizations. This book has hundreds of cross-referenced entries, from A to Z, in the dictionary and a list of acronyms with their corresponding definitions. The extensive chronology shows who did what and when and the introduction traces the often difficult circumstances African American performers faced compared to the more satisfactory present situation. Finally, the bibliography is useful to those readers who want to know more about specific topics or persons.
Keywords: 1-TV; 2-Histoire/Historiographie critique; 2-Étude des représentations; 3-Amérique du Nord (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 5-Auteur.rice PANDC; 5-Auteur.rice noir.e; 5-Autrice; _Nettoyé; États-Unis (corpus analysé); États-Unis (lieu de production du savoir)

Pretty Liar: Television, Language, and Gender in Wartime Lebanon - Khazaal, Natalie (Syracuse University Press, 2018)
"Pretty Liar" explores the rise of language and gender politics on Lebanese television to tell the untold story of the co-evolution of Lebanese television and its audiences and how the civil war of 1975-1991 affected that co-evolution. The shift in public interest in television has been widely acknowledged and interpreted within an institutional context as a victory of the neo-liberal entrepreneurship of a new, agile brand over the government inefficiency of Lebanon's national station, Télé Liban. Yet, the role of the Lebanese Civil War in reshaping national television and broadcasting in Arab media following the emergence of the Lebanese Broadcasting Company in 1985 has been unexplored. Based on empirical data and grounded in theory by Arab and global researchers, "Pretty Liar" offers textual analyses of five Lebanese fictional series, three major and several additional periodicals, and nine literary works, and provides context from unscripted interviews with television administrators, anchors, actors, and freelance contributors, print journalists, and audience members. Khazaal seeks to offer new insight into how entertainment television became a site for politics and political resistance, feminism, and the cradle for post-war Lebanon due to the shift in practices and standards of legitimacy. The history of television in Lebanon is not merely the history of technology and business, Khazaal argues, but rather the history of a people and their continuing quest for a responsive television even during times of civil unrest.
Keywords: 1-TV; 2-Approches sociologiques; 2-Histoire/Historiographie critique; 2-Théorie(s) et épistémologies des médias (media studies/médiologie/intermédialités); 2-Étude de la réception; 2-Étude des industries culturelles; 2-Étude des représentations; 3-Asie (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 5-Auteur.rice PANDC; 5-Autrice; Liban (corpus analysé); _Nettoyé; États-Unis (lieu de production du savoir)

Telly-Guillotined: How Television Changed India - Shah, Amrita (SAGE Publications India Pvt, Ltd., 2019)
Fist-fights in television studios, dwindling media autonomy, sensationalism, fake news, religious hate, abusive trolls, political spin ... How did we get here? Three decades ago, before economic liberalization, came the expansion and privatization of Indian television. Technological innovation and easing of government controls offered the prospect of journalistic independence, artistic creativity and an empowered citizenry. This was rendered illusory by runaway growth and untrammelled commercialization. In that thwarted promise of the late 20th century lie the seeds of Indian democracy's current crisis. Telly-Guillotined: How Television Changed India tells the story of how technology was usurped, first by propagandists, then by the market. Going behind the scenes of the world′s greatest media explosion, this book describes the impact of consumerism on the newsroom, the shaping of a new cultural politics and the rise of a new politics of seduction. In a landscape of technological innovation, blurred boundaries and sensory overload, Amrita Shah paints a picture of the Fourth Estate′s challenging future.
Keywords: 1-TV; 2-Approches sociologiques; 2-Histoire/Historiographie critique; 2-Théorie(s) et épistémologies des médias (media studies/médiologie/intermédialités); 2-Étude des industries culturelles; 3-Asie (corpus analysé); 4-Asie (lieu de production du savoir); 5-Auteur.rice PANDC; 5-Autrice; Inde (corpus analysé); Inde (lieu de production du savoir); _Nettoyé

Muy buenas noches: Mexico, Television, and the Cold War - Gonzalez de Bustamante, Celeste (Nebraska Paperback, 2013)
By the end of the twentieth century, Mexican multimedia conglomerate Televisa stood as one of the most powerful media companies in the world. Most scholars have concluded that the company’s success was owed in large part to its executives who walked in lockstep with the government and the Partido Revolucionario Institucional (PRI), which ruled for seventy-one years. At the same time, government decisions regulating communications infrastructure aided the development of the television industry. In one of the first books to be published in English on Mexican television, Celeste González de Bustamante argues that despite the cozy relationship between media moguls and the PRI, these connections should not be viewed as static and without friction. Through an examination of early television news programs, this book reveals the tensions that existed between what the PRI and government officials wanted to be reported and what was actually reported and how. Further, despite the increasing influence of television on society, viewers did not always accept or agree with what they saw on the air. Television news programming played an integral role in creating a sense of lo mexicano (that which is Mexican) at a time of tremendous political, social, and cultural change. At its core the book grapples with questions about the limits of cultural hegemony at the height of the PRI and the cold war.
Keywords: 1-TV; 2-Approches sociologiques; 2-Histoire/Historiographie critique; 2-Théorie(s) et épistémologies des médias (media studies/médiologie/intermédialités); 2-Étude des industries culturelles; 3-Amérique du Nord (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 5-Auteur.rice PANDC; 5-Autrice; Mexique (corpus analysé); _Nettoyé; États-Unis (lieu de production du savoir)

Prioritized: The Hip Hop (Re)Construction of Black Womanhood in Girlfriends and the Game - Lewis, Nghana (Watching While Black, 2012)
Why is it important that a Black woman created, wrote for, and co-produced¹ two highly-regarded television situation comedies that engaged a variety of Black women’s health issues while at the same time these issues were being reduced, simplified, or altogether ignored in mainstream American hip hop? Mara Brock Akil tacitly responded to this question when asked why four episodes of the third season of Girlfriends (2000–2008), the situation comedy she created and co-produced for UPN, addressed the HIV/AIDS crisis among Black women in America. “I have things I want to say,” explained Brock Akil, “about bridging television’s gap between
Keywords: 1-TV; 2-Approches sociologiques; 2-Genre et sexualité; 2-Histoire/Historiographie critique; 2-Étude des représentations; 3-Amérique du Nord (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 5-Auteur.rice PANDC; 5-Auteur.rice noir.e; 5-Autrice; _Nettoyé; États-Unis (corpus analysé); États-Unis (lieu de production du savoir)

“Hey, Hey, Hey!”: Bill Cosby’s Fat Albert as Psychodynamic Postmodern Play - Russworm, TreaAndrea M. (Watching While Black, 2012)
Although the cartoon series Fat Albert and the Cosby Kids (CBS, 1972–1984) averaged only nine new episodes a year during its twelve-year run (compared to a more standard production cycle of twenty-five to sixty new episodes a year for other cartoons), the show remained a highly popular option for young viewers on late Saturday mornings. By the time of the series’ network premiere in 1972, the cartoon’s animated African American stars—Weird Harold, Dumb Donald, Fat Albert, Rudy, Mushmouth, Bucky, Russell, and Bill—were familiar and recognizable to American audiences as originating from Bill Cosby’s boyhood community of North
Keywords: 1-TV; 2-Approches sociologiques; 2-Histoire/Historiographie critique; 2-Étude des représentations; 3-Amérique du Nord (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 5-Auteur.rice PANDC; 5-Auteur.rice noir.e; _Nettoyé; États-Unis (corpus analysé); États-Unis (lieu de production du savoir)

Politics After Television: Hindu Nationalism and the Reshaping of the Public in India - Rajagopal, Arvind (Cambridge University Press, 2001)
In January 1987, the Indian state-run television began broadcasting a Hindu epic in serial form, The Ramayana, to nationwide audiences, violating a decades-old taboo on religious partisanship. What resulted was the largest political campaign in post-independence times, around the symbol of Lord Ram, led by Hindu nationalists. The complexion of Indian politics was irrevocably changed thereafter. In this book, Arvind Rajagopal analyses this extraordinary series of events. While audiences may have thought they were harking back to an epic golden age, Hindu nationalist leaders were embracing the prospects of neoliberalism and globalisation. Television was the device that hinged these movements together, symbolising the new possibilities of politics, at once more inclusive and authoritarian. Simultaneously, this study examines how the larger historical context was woven into and changed the character of Hindu nationalism.
Keywords: 1-TV; 2-Approches sociologiques; 2-Histoire/Historiographie critique; 2-Étude des industries culturelles; 3-Asie (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 5-Auteur.rice PANDC; Inde (corpus analysé); _Nettoyé; États-Unis (lieu de production du savoir)

Manufacturing the Gang: Mexican American Youth Gangs on Local Television News - Tovares, Raul Damacio (Greenwood Publishing Group, Incorporated, 2002)
Coverage of Mexican-American youth gangs has been a staple of local television news in the United States for decades, and its form and content have come to embody many journalistic cliches: the rising tide of violence, the spread of drug addiction, the alienated minority youth. But as this bold new study argues, these stories contain gross exaggerations that lead to the reinforcement of stereotypes about Mexican-American young people and the Mexican-American community in general. Indeed, the police and community leaders greatly influence the content of this coverage by deciding what information to make available to the news media, while reporters select certain sources and ignore others, thus slanting the story even further. Source: Publisher
Keywords: 1-TV; 2-Approches sociologiques; 2-Histoire/Historiographie critique; 2-Étude des représentations; 3-Amérique du Nord (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 5-Auteur.rice PANDC; _Nettoyé; États-Unis (lieu de production du savoir)

Television, Nation, and Culture in Indonesia - Kitley, Philip (Ohio University Press, 2014)
The culture of television in Indonesia began with its establishment in 1962 as a public broadcasting service. From that time, through the deregulation of television broadcasting in 1990 and the establishment of commercial channels, television can be understood, Philip Kitley argues, as a part of the New Order’s national culture project, designed to legitimate an idealized Indonesian national cultural identity. But Professor Kitley suggests that it also has become a site for the contestation of elements of the New Order’s cultural policies. Based on his studies, he further speculates on the increasingly significant role that television is destined to play as a site of cultural and political struggle.
Keywords: 1-TV; 2-Approches sociologiques; 2-Histoire/Historiographie critique; 2-Étude des industries culturelles; 3-Asie (corpus analysé); 4-Océanie (lieu de production du savoir); 5-Auteur.rice PANDC; Australie (lieu de production du savoir); Indonésie (corpus analysé); _Nettoyé

Consuming Halal Turkish Television in Indonesia: A Closer Look at the Social Responses Towards Muhteşem Yüzyıl - Rakhmani, Inaya; Zakiah, Adinda (Television in Turkey: Local Production, Transnational Expansion and Political Aspirations, 2020)
This chapter unpacks the tension between secular, modern values and conservative, Islamic interpretations within the Indonesian middle class by taking the consumption of Turkish popular cultural products as a case. The chapter explicates the social responses towards the first Turkish television drama aired on terrestrial, private television in Indonesia: The Magnificent Century (Muhtesṃem Yüzyıl/Abad Kejayaan). This chapter understands the reproduction of secular and conservative Islamic values, while in contestation, as a response to broader global, market-capitalist developments. It finds that in response to audience criticism regarding the “un-Islamic” portrayal of the epoch in the drama—specifically the depiction of women as concubines—television stations enlisted the services of Muslim clerics to correct or justify the representation of historical facts. This reveals that market-driven self-censorship has opened up ways for Muslim clerics to influence television content. As such, the chapter argues that market-capitalist forces discursively use Islamic authority as a way to legitimise the halal consumption of Turkish drama among Indonesian Muslim audience at the expense of programme diversity.
Keywords: 1-TV; 2-Approches sociologiques; 2-Genre et sexualité; 2-Histoire/Historiographie critique; 2-Étude des industries culturelles; 2-Étude des représentations; 3-Asie (corpus analysé); 3-Europe (corpus analysé); 4-Asie (lieu de production du savoir); 5-Auteur.rice; 5-Auteur.rice PANDC; Indonésie (corpus analysé); Indonésie (lieu de production du savoir); Turquie (corpus analysé); _Nettoyé